2005
DOI: 10.1007/s10517-005-0424-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human VEGF165 Gene for Therapeutic Angiogenesis in Coronary Patients: First Results

Abstract: The paper presents the first results of therapeutic angiogenesis in clinical cardiosurgery: human VEGF(165) gene transplantation to coronary patients. The use of this therapeutic method is particularly effective in patients with inoperable cardiovascular injuries, i.e. patients with the most severe condition, in whom treatment remains little effective at the modern level of cardiosurgery development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Other previous reports used the same therapy, but in association with coronary artery bypass surgery, among others [7][8][9][10][11][12][13][14][15][16][19][20][21]. Two previous studies [17,18] similar to ours in that respect showed controversial results, one showing an improvement of myocardial perfusion and angina [17] and another only improvement in angina [18].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Other previous reports used the same therapy, but in association with coronary artery bypass surgery, among others [7][8][9][10][11][12][13][14][15][16][19][20][21]. Two previous studies [17,18] similar to ours in that respect showed controversial results, one showing an improvement of myocardial perfusion and angina [17] and another only improvement in angina [18].…”
Section: Discussionmentioning
confidence: 78%
“…Three months after intervention we observed improvements in scintigraphic SSS scores (18.38 ± 7.51 vs. 15.31 ± 7.29, P = 0.003) and SRS (11.92 ± 7.49 vs. 8.53 ± 6.68, P = 0.002) but not in proportion to the areal extent of ischemic Rev Bras Cir Cardiovasc 2010; 25(3): 311-321 of administration of VEGF. Clinical trials bring controversial results, many showing evidence of clinical improvement and angiogenesis [8][9][10][11][12][13][14][15][16][17][18][19] and others showing no differences in myocardial perfusion when compared to their controls [7,20]. Thus, although promising, remain still not completely clear the clinical effects on the myocardium vascularization of the therapy with VEGF in its various forms and ways of administration, justifying further studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to energy and spectral characteristics of the laser, myocardial parameters, and methods of appli cation, TMLR falls into categories [7,8]:…”
Section: Tmlr Methodsmentioning
confidence: 99%
“…VEGF165 is a predominantly expressed VEGF isoform, which plays a central role in vascular development [15]. In 2002 plasmid construct containing human VEGF165 gene was recommended for clinical use [16].…”
Section: Adenoviral Vectors Generationmentioning
confidence: 99%